2010
DOI: 10.1074/jbc.m110.138446
|View full text |Cite
|
Sign up to set email alerts
|

Insect Cytokine Paralytic Peptide (PP) Induces Cellular and Humoral Immune Responses in the Silkworm Bombyx mori

Abstract: In the blood (hemolymph) of the silkworm Bombyx mori, the insect cytokine paralytic peptide (PP) is converted from an inactive precursor to an active form in response to the cell wall components of microorganisms and contributes to silkworm resistance to infection. To investigate the molecular mechanism underlying the up-regulation of host resistance induced by PP, we performed an oligonucleotide microarray analysis on RNA of blood cells (hemocytes) and fat body tissues of silkworm larvae injected with active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 48 publications
3
72
0
Order By: Relevance
“…RH2180-5, using a silkworm model of infection (3). Injection of yeast β-glucans and bacterial peptidoglycans into the silkworm Bombyx mori induces maturation of the insect cytokine paralytic peptide, which results in muscle contraction of the larvae (4,5). We established an assay using the silkworm based on muscle contraction, which is associated with activation of innate immunity (6), and purified a polysaccharide with innate immunestimulating activity from green tea extracts (7).…”
Section: Introductionmentioning
confidence: 99%
“…RH2180-5, using a silkworm model of infection (3). Injection of yeast β-glucans and bacterial peptidoglycans into the silkworm Bombyx mori induces maturation of the insect cytokine paralytic peptide, which results in muscle contraction of the larvae (4,5). We established an assay using the silkworm based on muscle contraction, which is associated with activation of innate immunity (6), and purified a polysaccharide with innate immunestimulating activity from green tea extracts (7).…”
Section: Introductionmentioning
confidence: 99%
“…The status of Wolbachia in A. domesticus is unknown because no previous studies regarding this matter have been reported. In addition, there were also no Ishii et al (2010), have been heavily focused on specific AMPs extracted from various insects species and then tested on pathogenic agents in order to prove their significance for the regulation of antimicrobial activity. Cytryńska et al (2006) reported that eight peptides isolated and purified from Galleria mellonella were able to induce antimicrobial activity when tested against gram-negative and gram-positive bacteria, yeast, and filamentous fungi.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Functionally, spätzle binds with Toll to activate the pathway [84], whereas, paralytic peptide activates the DOPA decarboxylase (DDC) of the melanisation pathway [85,86] indicating that both specific (Toll) and non-specific (melanisation) immune reactions have diverged synchronously in the B. mori immune system.…”
Section: Phylogenetic Analysismentioning
confidence: 99%